Intellectual capital efficiency and credit risk in Sub-Saharan African banks - Mohd ‘Atef Md Yusof, Murtala Aliyu Ibrahim, (Opción, 2019)
The purpose of this paper is to study the relationship between intellectual capital (IC) and credit risk of Sub-Saharan African (SSA) banks and also test the modified models of Value Added Intellectual Coefficient (VAICTM). The results show no relationship between IC and credit risk. The problem of inadequacy in the reporting IC and its components and the availability of data on various proxies is one of the major challenges in the study. The VAICTM and the extended r-VAICTM models can be useful tools in the evaluation of bank performance.